Characterization of Human Hippocampal Neural Stem/Progenitor Cells and Their Application to Physiologically Relevant Assays for Multiple Ionotropic Glutamate Receptors. (September 2014) - Fukushima, Kazuyuki; Tabata, Yoshikuni; Imaizumi, Yoichi; Kohmura, Naohiro; Sugawara, Michiko; Sawada, Kohei; Yamazaki, Kazuto; Ito, Masashi
The hippocampus is an important brain region that is involved in neurological disorders such as Alzheimer disease, schizophrenia, and epilepsy. Ionotropic glutamate receptors—namely, N -methyl-D-aspartate (NMDA) receptors (NMDARs), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptors (AMPARs), and kainic acid (KA) receptors (KARs)—are well known to be involved in these diseases by mediating long-term potentiation, excitotoxicity, or both. To predict the therapeutic efficacy and neuronal toxicity of drug candidates acting on these receptors, physiologically relevant systems for assaying brain region–specific human neural cells are necessary. Here, we characterized the functional differentiation of human fetal hippocampus–derived neural stem/progenitor cells—namely, HIP-009 cells. Calcium rise assay demonstrated that, after a 4-week differentiation, the cells responded to NMDA (EC50 = 7.5 ± 0.4 µM; n = 4), AMPA (EC50 = 2.5 ± 0.1 µM; n = 3), or KA (EC50 = 33.5 ± 1.1 µM; n = 3) in a concentration-dependent manner. An AMPA-evoked calcium rise was observed in the absence of the desensitization inhibitor cyclothiazide. In addition, the calcium rise induced by these agonists was inhibited by antagonists for each receptor—namely, MK-801 for NMDA stimulation (IC50 = 0.6 ± 0.1 µM; n = 4) and NBQX for AMPA and KA stimulation (IC50 = 0.7 ± 0.1 and 0.7 ± 0.03 µM, respectively; n = 3). The gene expression profile of differentiated HIP-009 cells was distinct from that of undifferentiated cells and closely resembled that of the human adult hippocampus. Our results show that HIP-009 cells are a unique tool for obtaining human hippocampal neural cells and are applicable to systems for assay of ionotropic glutamate receptors as a physiologically relevant in vitro model.